Studies on gasification of corncobs and its utilization - Allen, Deuel H.
The endeavor to expand the energy based led to several studies on the utilization of offals from agriculture and forest products. Although there were studies on the utilization of ipil-ipil wood, charcoal, coconut shells, coir fibers and rice husks, most of them tried to study ways and means of efficiently converting biomass into salable energy in the form of producer gas.
This study was an investigation on the gasification of corncobs in fixed-bed producers and ways of utilizing the producer gas. The study included a search of a suitable gas-producer for corncobs, application of conventional methods in cleaning the producer gas, and a method of estimating the amount of diesel oil that could be displaced if producer gas was utilized in stationary diesel engines.
In this study, there were different designs of gas producers that were tested, four of them were downdraft suction types and one was downdraft pressure type. The method of testing the gas-producers was done on two experimental set-ups. The first experimental set-up consisted of using producer gas in a stationary diesel engine while the second set-up utilized the producer gas in a converted oil-fired furnace. In general, corncobs proved to be a good biomass fuel for gas-producers. It has a fairly high calorific value and low ash content. Moreover, corncobs which are uniformly sized are important for gasification in a fixed-bed gas generators. However, tar was the main problem in utilizing the producer gas in internal combustion engines. The problem of separating tar from the gas was solved by providing an efficient gas cleaning device called the wet filter.
Preliminary to the study, corncobs were tested for their combustion characteristics. These preliminary studies yielded results on the proximate analysis of corncobs and the heating value of corncobs on dry basis. The analysis of producer ags was not made to lack of necessary gas analyzer, so that the project was limited only to computer-aided-estimate of diesel oil savings in diesel engines using producer gas. The calorific value of the producer gas was not determined, but an estimate was deduced from the amount of diesel oil savings attained by utilizing the gas in diesel engines.
The thesis included an extensive survey of the gasification of coal and some of the known utilization of the fuel gas. Some works in the gasification of agricultural waste and forest products were also mentioned.
Thesis (M.S. Mechanical Engineering)--University of the Philippines, Diliman
Keywords: Corncobs gasification; Corncobs-utilization.